Cell Cycle Dynamics in a Response/Signaling Feedback System With Overlap - Moses, Gregory; Scalfano, Denise (Journal of Applied Nonlinear Dynamics, 2026)
We continue our study of the dynamics of the yeast cell division cycle, in particular a feedback model where cells in one fixed part of the cycle, the Signaling region, affect the growth of cells in another part of the cycle, the Responsive region. This causes cells to cluster together as they pass through their cell division cycles, a known biological phenomenon that had been previously unexplained. In previous work, these regions were assumed to have disjoint interiors. We consider the dynamics when oscillators are coupled directly to themselves by allowing the responsive and signaling regions to overlap. We see that although the dynamics in an important subspace are largely preserved, the dynamics of the system in the full phase space exhibit less clearly quantifiable behavior. While in previously studied models, stability in the clustered subspace implies stability in the full phase space, here this is not the case, and the clustered subspace only unreliably predicts the behavior in the full phase space.